The prevalence and distribution of Multiple Sclerosis in Poland and around the world - Guzik, Agnieszka; Kwolek, Andrzej (European Journal of Clinical and Experimental Medicine, 2026)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Multiple Sclerosis (MS) is a chronic demyelinating disease of the nervous system affcting mostly young adults and predominately women. The exact cause of MS is not known. It is assumed that this is a multifactorial disease which is caused probably not by a single factor but several coexisting factors. The prevalence of MS on the globe is irregular and associated with latitude. Increased incidence is recorded in the latitudes with cool and temperate climate than in tropical and subtropical ones. Number of people with MS all over the world exceeds 2.5 million and about 630,000 cases were reported in Europe. Poland is among the countries with high incidence of MS. It is assumed that the incidence of MS in Poland ranges from 45 to 92 people per 100,000 inhabitants. The disease onset is usually between 20 and 40 years of age at the time of greatest professional activity. MS is one of the most common causes of long-term incapacity for work and therefore it is not only signifiant health, but also social problem. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Aim: The aim of this study is to assess the prevalence and distribution of Multiple Sclerosis in Poland and around the world. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Method: A review of domestic and foreign literature in the years 2008-2014 was conducted. The following databases were searched: PubMed, Science Direct, Termedia, Polska Bibliografi Lekarska.